1996
DOI: 10.1103/physrevd.53.2227
|View full text |Cite
|
Sign up to set email alerts
|

(2+1)-dimensional QED with dynamically massive fermions in vacuum polarization

Abstract: We study chiral symmetry breaking in three-dimensional QED with Nf flavors of four-component fern&ns. A closed system of Schwinger-Dyson equations for fermion and photon propagators and the full fermion-photon vertex is proposed, which is consistent with the Ward-Takahashi identity. A simplified version of that set of equations is reduced (in the nonlocal gauge) to the equation for a dynamical fermion mass function, where the one-loop vacuum polarization with dynamically massive fermions has been taken into ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 26 publications
3
58
0
Order By: Relevance
“…For example, in a paper [20] these ansatze were used to solve a coupled system of DSE for the photon and fermion propagators and to get an estimate for a critical number N c for chiral symmetry breaking in QED3. Although such an approach reproduces the value N c ≈ 4 close to the value N c found in leading order of the 1/N expansion [16][17][18], it cannot be considered as a reliable one since the approach does not permit to identify the ansatz with a class of Feynman diagrams. Also one cannot estimate corrections terms to results obtained in this approach.…”
Section: )mentioning
confidence: 82%
See 1 more Smart Citation
“…For example, in a paper [20] these ansatze were used to solve a coupled system of DSE for the photon and fermion propagators and to get an estimate for a critical number N c for chiral symmetry breaking in QED3. Although such an approach reproduces the value N c ≈ 4 close to the value N c found in leading order of the 1/N expansion [16][17][18], it cannot be considered as a reliable one since the approach does not permit to identify the ansatz with a class of Feynman diagrams. Also one cannot estimate corrections terms to results obtained in this approach.…”
Section: )mentioning
confidence: 82%
“…Numerous papers using this approach gave the results for the value of N c in the range 2 < N c < 5 [7,[16][17][18][19][20]. Renormalization group studies give the critical value N c approximately in the same range [21,22] with possible existence of a third intermediate phase for…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that, in noncompact QED with fermions, the phase diagram is dependent on the number of flavors and that, at weak coupling, chiral symmetry is broken only for a small number (less than about 3.5) of fermions [17,18,19,20]. (A recent description of the status of three-dimensional QED can be found in [21,22].) It is quite probable that, at weak coupling, both the compact and non-compact formulations have quite similar properties.…”
Section: The Modelmentioning
confidence: 99%
“…(26)) or N c as a function of the ratio πe 2 /µ (α = N e 2 /8) with the numerical solution of the integral equation (1) which was obtained by using numerical methods described in Ref. [24]. Basically, starting with some initial guess for Σ(p), the integral equation is iterated using splines on a logarithmic momentum scale, until sufficient precision is reached.…”
Section: The Gap Equation Of Massless Qedmentioning
confidence: 99%